Genetic Evaluation of Patients With Delayed Puberty and Congenital Hypogonadotropic Hypogonadism: Is it Worthy of Consideration? - Festa, Adalgisa; Umano, Giuseppina Rosaria; Miraglia del Giudice, Emanuele; Grandone, Anna (Frontiers in Endocrinology, 2020)
Delayed puberty is a common reason of pediatric endocrinological consultation. It is often a self-limited (or constitutional) condition with a strong familial basis. Type of inheritance is variable but most commonly autosomal dominant. Despite this strong genetic determinant, rarely mutations in genes implicated in the regulation of hypothalamic-pituitary-gonadal axis have been identified in cases of self-limited delayed puberty and often in relatives of patients with congenital hypogonadotropic hypogonadism (i.e. FGFR1 and GNRHR genes). However recently, next generation sequencing analysis has led to discovery of new genes (i.e. IGSF10, HS6ST1, FTO and EAP1) implicated in determining isolated self-limited delayed puberty in some families. Despite the heterogeneity of genetic defects resulting in delayed puberty, genetic testing may become an useful diagnostic tool for the correct classification and management of patients with delayed puberty. This article will discuss the benefits and the limitations of genetic testing execution in cases of delayed puberty.